Rain water composition at two BAPMoN stations in India (MAUSAM, 1998)
Six years of rain water composition data from two BAPMoN regional stations in India are analysed using Factor Model Analysis. It gives four factors representing different source type contributing to water soluble pollutants in precipitation. The major influence on rain water composition at both sites are Sea-salt and continental source such as soil dust, ammonia and low levels of sulfate and nitrate which presumably have both natural and anthropogenic components. The long term mean values of pH of rain water at both sites were found to be greater than the pH value of selected polluted northern atmosphere sites.